Phylogenetic analysis of classical swine fever virus (CSFV) by cloning and sequencing of partial 5’ non-translated genomic region - SINGH, V K; SAIKUMAR, G; BANDYOPADHYAY, S K; PALIWAL, O P (The Indian Journal of Animal Sciences, 2014)
Classical swine fever (CSF) is an economically important and highly contagious viral disease of pigs across the world. Despite its office International des Epizooties (OIE) list A status, the disease has not been studied extensively in India and epidemilogical and phylogenetic information with regards to CSFV is lacking. In the present study, an attempt was made towards phylogenetic characterization of virulent (CSFV/MP) and lapinized vaccine (CSF/LAP) strains of CSFV. Reverse transcription-polymerase chain raction (RT-PCR) amplified products from 5’non-translated region (NTR) of both the strains were cloned and sequenced. The truncated genomic sequences were analyzed and compared with published CSFV sequences using LASERGENE and PHYLIP softwares. Phylogenetic analysis resulted into placement of CSFV/MP and CSFV/LAP strains into genorgroup 1.1. The present study provides phylogenetic information and paves way for large scale molecular epidemological studies with respect to CSF in India.